Optimization and characterization of new oleogels developed based on sesame oil and rice bran oil - Sivakanthan, S.; Fawzia, S.; Mundree, S.; Madhujith, T.; Karim, A. (Elsevier, 2023)
In recent years, there has been a surge of interest in oleogels as a promising low-saturated and trans fat free alternative to traditional solid fats. However, to date, oleogels made from different edible oils using different gelator molecules have minimum commercial application due to the lack of mimicking the properties of con- ventional solid fats. This study aimed to optimize the formulation of oleogels with properties close to commercial margarines based on binary mixtures of sesame oil and rice bran oil using beeswax and stearic acid as oleoge- lators. An Extreme Vertices Design with four components: sesame oil, rice bran oil, beeswax, and stearic acid, and 32 runs was developed using Minitab 21.1. Multi-response optimization was performed based on rheological parameters, and oil binding capacity as responses. All responses for optimization had R2 values > 96%. The oil binding capacity of the optimized oleogel was 99.99%. Optimized oleogel was further characterized for rheo- logical, thermal, microstructural, and molecular properties and compared with commercial margarines. Results show that the properties of the optimized formula had closer values to those of commercial margarines, however with less structural recovery ability. Optimized oleogel exhibited higher oxidative stability than the margarine, however, lower than the oils. Beeswax and stearic acid exhibited synergistic effects on the oleogel properties at the ratio of 3:1. Results indicate that the optimized oleogel has the potential to be used in margarine manufacture with further developments to improve the gel strength and oxidative stability of the oleogel.
Keywords: Beeswax; Oleogel; Optimization; Rice bran oil; Sesame oil; Stearic acid